Concentration of lead, cadmium and mercury in the blood of human and sheep in the different governorate of Iraq - ALSalman, Mazin Raad Mahmood; Dawood, Tamara Natik (Journal of Kerbala for Agricultural Sciences, 2023)
This study was conducted to find out the concentration of heavy metals (lead, cadmium, and mercury) in human and sheep blood along the Tigris River (Mosul, Salahuddin, Baghdad, Wasit, and Misan). Blood samples were taken from different regions to study the effect of heavy metal pollutants on human and sheep health. Lead and cadmium concentrations in the blood of humans and sheep in Baghdad, Mousel, and Misan governorates were significantly (P< 0.05) higher compared with their concentrations in other governorates; on the other hand, the concentration of lead in the blood of humans and sheep was lowest in Wasit governorate. Mercury were significantly higher (P<0.05) only in blood of the human and sheep in Misan governorate.